Efficient perovskite solar cells by metal ion doping - Wang, Jacob Tse-Wei; Wang, Zhiping; Pathak, Sandeep; Zhang, Wei; deQuilettes, Dane W.; Wisnivesky-Rocca-Rivarola, Florencia; Huang, Jian; Nayak, Pabitra K.; Patel, Jay B.; Yusof, Hanis A. Mohd; Vaynzof, Yana; Zhu, Rui; et al. (Energy & environmental science, 2016)
Realizing the theoretical limiting power conversion efficiency (PCE) in perovskite solar cells requires a better understanding and control over the fundamental loss processes occurring in the bulk of the perovskite layer and at the internal semiconductor interfaces in devices. One of the main challenges is to eliminate the presence of charge recombination centres throughout the film which have been observed to be most densely located at regions near the grain boundaries. Here, we introduce aluminium acetylacetonate to the perovskite precursor solution, which improves the crystal quality by reducing the microstrain in the polycrystalline film. At the same time, we achieve a reduction in the non-radiative recombination rate, a remarkable improvement in the photoluminescence quantum efficiency (PLQE) and a reduction in the electronic disorder deduced from an Urbach energy of only 12.6 meV in complete devices. As a result, we demonstrate a PCE of 19.1% with negligible hysteresis in planar heterojunction solar cells comprising all organic p and n-type charge collection layers. Our work shows that an additional level of control of perovskite thin film quality is possible via impurity cation doping, and further demonstrates the continuing importance of improving the electronic quality of the perovskite absorber and the nature of the heterojunctions to further improve the solar cell performance.
Gesehen am 05.06.2020